Perbandingan PerekembanganAdministrasi Publik di Australia dan Indonesia dalam E-Goverment - Eka Prastyo; Aminullah Aminullah (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
The development of e-Government has become a key strategy in modernizing public administration in various countries, including Australia and Indonesia. The application of information and communication technology in government administration aims to improve bureaucratic efficiency, the quality of public services, and realize the principles of good governance. This study aims to analyze and compare the development of public administration in the implementation of e-Government in Australia and Indonesia. The research method used is a qualitative approach with a literature review of relevant and accessible scientific journals, academic books, and policy documents. The results show that Australia has a higher level of e-Government maturity, characterized by good digital service integration, infrastructure readiness, and adequate human resource capacity. Meanwhile, Indonesia has shown significant progress through the implementation of the Electronic-Based Government System (SPBE), but still faces challenges such as infrastructure gaps, limited apparatus competency, and fragmented service systems. This research is expected to contribute concepts to the development of e-Government policies and public administration reform in Indonesia.